Hubungan smartphone addiction dan self efficacy dengan kecemasan matematika siswa SMA - Siti Nadiatul Istiqomah; Asih Miatun (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study aims to determine whether there was a correlation between smartphone addiction and self-efficacy with student questions in high school when face-to-face learning is limited. This was a quantitative study that employed correlational research methods. The population for this study was drawn from all students of SMAN 93 Jakarta, and a sample of 254 students was obtained using the Slovin formula. In this study, a questionnaire was employed as the instrument. The data analysis used in this research is descriptive analysis, classical assumption test (homogeneity test, multicollinearity test, heteroscedasticity test), and hypothesis testing (multiple linear regression test, coefficient of determination test, F-test, and T-test). Smartphone addiction and self-efficacy were found to be responsible for 72.03% of anxiety, there was a positive correlation between smartphone addiction and math questions, and a negative correlation between self-efficacy and mathematics anxiety. Therefore, there was a correlation between smartphone addiction and self-efficacy with mathematics in senior high students.